DESIGN OF ONLINE-BASED STUDY PROGRAM DETERMINATION APPLICATION - Alviani, Vera; Ramdana, R (Omnia Tempus, 2022)
Application simulation for determining study programs based on online and implementing simulations to assist prospective students in choosing study programs at STMIK AKBA Makassar. The tests in this thesis include the DAT (Differential Attitude Test) test. Making this simulation using the PHP programming language and using the Bootstrap Framework where the database uses the MySql database. System testing has been carried out using the Black Box testing method. The results of this study indicate that this application can run well. This simulation does not precisely provide a decision on the problems faced by prospective students in determining the study program but only complements information before making a decision.